2021
DOI: 10.3390/cells10123523
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End-Products (AGEs) and Their Soluble Receptor (sRAGE) in Women Suffering from Systemic Lupus Erythematosus (SLE)

Abstract: Systemic lupus erythematosus (SLE) is characterized by abnormal action of the immune system and a state of chronic inflammation. The disease can cause life-threatening complications. Neoepitopes arising from interdependent glycation and oxidation processes might be an element of SLE pathology. The groups included in the study were 31 female SLE patients and 26 healthy female volunteers (the control group). Blood serum samples were obtained to evaluate concentrations of advanced glycation end-products (AGEs), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…It may partially explain the observed lack of correlations between the PASI values and the concentrations of CML and CEL. It seems that CML and CEL are good markers of glycation in psoriasis, contrary to e.g., systemic lupus erythematosus [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may partially explain the observed lack of correlations between the PASI values and the concentrations of CML and CEL. It seems that CML and CEL are good markers of glycation in psoriasis, contrary to e.g., systemic lupus erythematosus [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed excessive production of ROS, along with many other factors may induce SLE [ 22 ]. Increase in cell death and delay in clearance of these dead cells, as well as apoptotic cells are commonly associated with SLE induced excessive production of ROS [ 23 , 24 ].There are evidences of link between oxidative stress, generation of AGEs and SLE [ 25 - 27 ]. Complex and unwarranted reactions may cause the formation of AGEs, which are identified by the immune system as neoepitopes [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The content of AGEs in the skin of haemodialysis patients is significantly higher than that of healthy individuals ( 33 , 41 ). Patients with severe psoriasis ( 42 ), diabetes and insulin resistance (IR) syndrome ( 43 , 44 ), and systemic lupus erythematosus ( 45 , 46 ) exhibit exacerbated production of endogenous AGEs, and the levels of AGEs in their skin were higher than those in the control group due to their persistent chronic inflammation, hyperglycaemia, or oxidative stress. In clinically, due to the differences in AGEs expression among these diseases that the skin fluorescence AGEs can utilised to predict the occurrence of diseases such as diabetes, renal or cardiovascular diseases ( 47 ).…”
Section: Brief Biochemistry Of Advanced Glycation End Productsmentioning
confidence: 99%